2006
DOI: 10.1139/l05-090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coarse aggregate size on strength and workability of concrete

Abstract: The properties of concrete were studied when the proportions of 37.5 and 19.5 mm stone in the coarse aggregate were varied. With the cement content of 160 kg/m3 and the ratio of water/cement (w/c) greater than 0.9, the compressive strength is maximum at 25 percent by weight (w/o) of 37.5 mm stone. Conversely, for the cement content of 350 kg/m3 and w/c ratios of less than 0.50, maximum compressive strength is substantively reduced. For both 160 kg/m3 and 350 kg/m3 cement contents, workability improves slightly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 1 publication
1
15
0
Order By: Relevance
“…This phenomenon can be explained by the physical entanglement of aggregates that contributes to compressive strength and fracture energy of concrete and that is more pronounced with larger aggregates [25,26]. These results are coherent with those observed in the literature [21][22][23][24][25][26].…”
Section: Unconfined Compression Testssupporting
confidence: 84%
“…This phenomenon can be explained by the physical entanglement of aggregates that contributes to compressive strength and fracture energy of concrete and that is more pronounced with larger aggregates [25,26]. These results are coherent with those observed in the literature [21][22][23][24][25][26].…”
Section: Unconfined Compression Testssupporting
confidence: 84%
“…The outcome of this study shows that strength ratio was increases when the nominal maximum aggregate size is increases in the concrete at each testing date and the strength ratio decreased when nominal maximum aggregate size is decreased. Tumidajski and Gong (3) in their research studied the variation of compressive strength and workability of concrete with the size of coarse aggregate.In their study the concrete was made by using different proportions of 37.5 and 19.5 mm stones as coarse aggregate. Their test results show that by using cement content of 160 kg/m 3 and (w/c) greater than 0.9, the compressive strength is maximum at 25 percent by weight of 37.5 mm stone.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the loading rate, coarse aggregate size, and water-cement ratio have a greater impact on the compressive properties of concrete. 20,21 Therefore, seven groups of specimens were designed for the three different variables mentioned above, and there are three specimens for each of the seven groups. The mix proportions and design variables of different RAC specimens are summarized in Table 1.…”
Section: Sample Preparationmentioning
confidence: 99%